The Effect of Removing Superior Temporal Cortical Motion Areas in the Macaque Monkey: I. Motion Discrimination Using Simple Dots. - Cowey, A; Marcar, V (1992)
We compared the pre- and postoperative performance of macaque monkeys on visual discrimination tasks entailing the perception of differences in the motion of two luminous spots. Animals in which area MT and adjacent regions had been surgically removed were not significantly impaired as long as there were differences in the temporal frequency of the two stimuli. When the latter were eliminated the postoperative performance of the MT animals was significantly impaired compared to their preoperative performance and compared to the animals in the control groups. The same animals were also impaired at perceiving which of two moving dots, presented in the dark, changed its direction.